2020
DOI: 10.1177/2399808320941860
|View full text |Cite
|
Sign up to set email alerts
|

The Spanish spatial city size distribution

Abstract: This paper analyses the Spanish city size distribution from a new perspective, focusing on the role played by distance. Using un-truncated data from all cities in 1900 and 2011, we study the spatial distribution of cities and how the city size distribution varies with distance. First, K-densities are estimated to identify different spatial patterns depending on city size, with significant patterns of dispersion found for medium-sized and large cities. Second, using a distance-based approach that considers all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…Frontiers in Built Environment frontiersin.org represented by the Pareto distribution (Jiang and Jia, 2011;Chen, 2016;González-Val, 2020), whereas in India, China, and Japan, the distribution shows a transition from a lognormal distribution in the early periods to Pareto in later periods (Kuninaka and Matsushita, 2008;Luckstead and Devadoss, 2014;Li and Zhang, 2018). In recent years, research has been more in-depth; researchers have discussed the urban size from a mixture of a lognormal distribution and Pareto distribution (Luckstead et al, 2017;Băncescu et al, 2019).…”
Section: Hypothesis Of the Double Pareto Lognormal Distributionmentioning
confidence: 99%
“…Frontiers in Built Environment frontiersin.org represented by the Pareto distribution (Jiang and Jia, 2011;Chen, 2016;González-Val, 2020), whereas in India, China, and Japan, the distribution shows a transition from a lognormal distribution in the early periods to Pareto in later periods (Kuninaka and Matsushita, 2008;Luckstead and Devadoss, 2014;Li and Zhang, 2018). In recent years, research has been more in-depth; researchers have discussed the urban size from a mixture of a lognormal distribution and Pareto distribution (Luckstead et al, 2017;Băncescu et al, 2019).…”
Section: Hypothesis Of the Double Pareto Lognormal Distributionmentioning
confidence: 99%
“…Previous researches have shown that trajectories in human society exhibit the statistically similar Lévy ight characteristics, such as the traces of bank note [12], human mobility [13], and COVID-19 con rmed cases [14]. Many studies have shown that the rank-order of cities in the United States [15], India [16], and Spain [17] shows Lévy ights characteristics, following Pareto law [15,18] or Zipf's law [19,20]. Researchers have also employed power-law adjusted metropolitan indicators [21] to assess urban land use efficiency in Chinese cities.…”
Section: Introductionmentioning
confidence: 97%
“…is paper covers the most commonly used data types for measuring urban development [17]. Firstly, it is clear that the research object is the steplengths of urban development trajectory [25], with economical development as horizontal axis and social development as vertical axis.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the intimate pattern of population distribution and accounting for the intrinsic socioeconomic dynamics of urban-rural hierarchies, are key arguments of applied economics, regional science, spatial planning, and political geography [1][2][3]. By considering population, settlements, and activities, both separately and together, comparative analyses of urban-rural hierarchies that use population (or economic) data at different aggregation levels were rather infrequent in both advanced economies and emerging countries [4][5][6]. The need for coherent, high-quality statistics limits the practical applicability of theoretical Land 2024, 13, 415 2 of 15 exercises referring to the rank-size relationship and, more specifically, to the empirical verification of Zipf's law for specific variables, basically population or, less frequently, settlements and activities [7][8][9].…”
Section: Introductionmentioning
confidence: 99%